Effect of Avocado Leaves Extract on Creatinin and Urea Levels in Rats Induced NaCl and Prednison - Najwa, Hilya U.; Elisa, Novi; Puspitaningrum, Ika; Anggraeny , Ebta N.; Sundoro, Aries K. (Jurnal Akademika Kimia, 2023)
Creatinine and urea are metabolic waste substances excreted by the kidneys. Kidneys excrete metabolic waste substances. Renal dysfunction is associated with the increased level of creatinine and urea in the blood. The ethanolic extract of avocado leaves (Persea americana Mill.) contains flavonoid compounds, alkaloids, tannins, saponins, and steroids which act as antioxidants and antihypertensive. It is known to reduce creatinine and urea levels in the blood. The animal model was divided into five groups: normal control, negative control (CMC - Na 0.5 %), and avocado leaves ethanolic extract group with doses of 75, 150, and 250 mg/kg BW rats. All groups except the normal control group were induced by oral administration of NaCl solution 2 % and prednisone suspension 1.5 mg/kg BW rats for 21 days and following treatment by oral administration for 7 days based on its group. Flavonoid compounds of avocado leave ethanolic extract identified as 5,7-di-OH-dihydroflavonol. Results show Kruskal - Wallis test between groups (p < 0.05) is significantly different. Concluded that administration of avocado leaves ethanol extract at doses of 75, 150, and 250 mg/kg BW rats might reduce creatinine levels, while avocado leaves ethanol extract at a dose of 250 mg/kg BW rats could reduce urea levels.